Involvement of intracellular transport in TREK-1c current run-up in 293T cells. Issue 3 (4th May 2017) - Andharia, Naaz; Joseph, Ancy; Hayashi, Mikio; Okada, Masayoshi; Matsuda, Hiroko
ABSTRACT: The TREK-1 channel, the TWIK-1-related potassium (K + ) channel, is a member of a family of 2-pore-domain K + (K2P) channels, through which background or leak K + currents occur. An interesting feature of the TREK-1 channel is the run-up of current: i.e. the current through TREK-1 channels spontaneously increases within several minutes of the formation of the whole-cell configuration. To investigate whether intracellular transport is involved in the run-up, we established 293T cell lines stably expressing the TREK-1c channel (K2P2.1) and examined the effects of inhibitors of membrane protein transport, N-methylmaleimide (NEM), brefeldin-A, and an endocytosis inhibitor, pitstop2, on the run-up. The results showing that NEM and brefeldin-A inhibited and pitstop2 facilitated the run-up suggest the involvement of intracellular protein transport. Correspondingly, in cells stably expressing the mCherry-TREK-1 fusion protein, NEM decreased and pitstop2 increased the cell surface localization of the fusion protein. Furthermore, the run-up was inhibited by the intracellular application of a peptide of the C-terminal fragment TREK335–360, corresponding to the interaction site with microtubule-associated protein 2 (Mtap2). This peptide also inhibited the co-immunoprecipitation of Mtap2 with anti-mCherry antibody. The extracellular application of an ezrin inhibitor (NSC668394) also suppressed the run-up and surface localization of the fusion protein. The co-application of these inhibitors abolished the TREK-1c current, suggesting that the additive effects of ezrin and Mtap2 enhance the surface expression of TREK-1c channels and the run-up. These findings clearly showed the involvement of intracellular transport in TREK-1c current run-up and its mechanism.